The Effect Of Objectivity, Independence And Professional Ethics On Audit Quality - Riyadi, Tomi; Supriatiningsih, Supriatiningsih; Suhadasyah , Muhammad Ardhan (Institut Bisnis dan Informatika Kesatuan, 2025)
The purpose of this study is to examine and analyze the impact of objectivity, independence, and professional ethics on audit quality. The data utilized in this research is primary data. The study's population consists of 63 auditors from Bekasi. Data was collected through questionnaires and interviews, and analyzed using the SPSS24 application. The independent variables in this study are objectivity, independence, and professional ethics, while the dependent variable is audit quality. The findings indicate that objectivity has a significant positive effect on audit quality. This suggests that a higher level of objectivity in auditors leads to an improvement in the quality of audits produced. Similarly, independence also has a significant positive effect on audit quality, meaning that the greater the auditor's independence, the higher the quality of the audit. Additionally, professional ethics has a significant positive impact on audit quality, indicating that a higher level of professional ethics in auditors contributes to better audit quality.